National laboratory policies and plans in sub-Saharan African countries: gaps and opportunities - Pascale Ondoa; Ankie van der Broek; Christel Jansen; Hilde de Bruijn; Constance Schultsz (AOSIS, 2017)
Background: The 2008 Maputo Declaration calls for the development of dedicated national laboratory policies and strategic plans supporting the enhancement of laboratory services in response to the long-lasting relegation of medical laboratory systems in sub-Saharan Africa. Objectives: This study describes the extent to which laboratories are addressed in the national health policies and plans created directly following the 2008 momentum for laboratory strengthening. Method: National health policies and plans from 39 sub-Saharan African countries, valid throughout and beyond 31 December 2010 were collected in March 2012 and analysed during 2013. Results: Laboratories were addressed by all countries. Human resources were the most addressed topic (38/39) and finances and budget were the least addressed (< 5/39). Countries lagging behind in national laboratory strategic planning at the end of 2013 (17/39) were more likely to be francophone countries located in West-Central Africa (13/17) and have historically low HIV prevalence. The most common gaps anticipated to compromise the implementation of the policies and plans were the disconnect between policies and plans, under-developed finance sections and monitoring and evaluating frameworks, absence of points of reference to define gaps and shortages, and inappropriate governance structure. Conclusion: The availability of laboratory policy and plan implementation can be improved by strictly applying a more standardised methodology for policy development, using harmonised norms to set targets for improvement and intensifying the establishment of directorates of laboratory services directly under the authority of Ministries of Health. Horizontal programmes such as the Global Health Security Agenda could provide the necessary impulse to take the least advanced countries on board.